Spiritualitas Diakonia Guru Pendidikan Agama Katolik (Sebuah Refleksi atas Panggilan Guru PAK di Tahun Diakonia) - Emanuel Haru (Jurnal Alternatif Wacana Ilmiah Interkultural, 2020)
A Catholic Religious Education Teacher is called to become a servant. He/She dedicate Him/Her self to present the Kingdom of God for others, wherever He/She work. Ruteng Diocese has decided the year of 2019 as Diacony Year. It is one of the implementations of Third Synod of this Diocese. Diacony is the preaching of the Church to serve all the creatures. The specialty of Diacony is presenting the Kingdom of God in concrete work in the fields of economics, politics, law, education, culture, including technology and the world of social communication.As thecitizens of the Church of God’s People, every person (and group of people) is called to carry out the mission of service that is to present the Kingdom in to the world in accordance with the professions and fields of duty entrusted to it. Likewise, a teacher. Teachers, including Catholic Religious Education Teachers who work in education field, have the responsibility to implement this year of service (diacony) through their specific duties as a teacher and educator as well as a catechist. Through his/her work as a teacher and educator, Catholic Religious Education Teachers present the Kingdom of God to students in the school. Likewise in carrying out its function as a catechist. He/She presents the kingdom of God to anyone wherever He/She works as a catechist.This paper is a reflection of the implementation of the duties of a Catholic Religious Education Teacher who must actually have a diacony spirituality. Diacony spirituality is inherent in a Catholic Religious Education Teacher when He/She is on a mission as a servant, not as a mere worker. In the context of interpreting this Year of service/diacony, there is a reflective question which is evocative and suing which is asked, “Is the Catholic Religious Education Teacher still aware of his calling as a minister with some virtues inherent in the ministry of service?